2017
DOI: 10.3389/fmats.2017.00037
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Local Volumetric Bone Mineral Density in Osteoarthritic Joints Is Associated with the Increase in Cartilage Damage: A Peripheral Quantitative CT Study

Abstract: Osteoarthritis (OA) is one of the most prevalent joint diseases, which causes pain and disability in the adult population. OA affects the osteochondral unit in the joints, which comprises both cartilage and subchondral bone. There has been some progress in understanding the changes in subchondral bone with progression of OA. However, local changes in subchondral bone such as microstructure or volumetric bone mineral density (vBMD) in connection with the defect in cartilage are relatively unexplored. To develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Several studies have reported subchondral bone plate (SBP) thinning and loss of subchondral trabecular bone (STB) in early OA [9][10][11][12] , with some suggestions that subchondral bone changes may precede changes in cartilage 13,14 . However, the hallmark features of end-stage OA comprise a thickening of the SBP 12,15,16 , together with increased bone volume fraction, increased trabecular thickness, and decreased trabecular separation in the STB [17][18][19][20] , lower bone mineralisation 21,22 and the presence of subchondral bone cysts (SBCs), and osteophytosis 23 . The aforementioned studies highlight overall trends in subchondral bone changes, but these studies have been primarily restricted to excised bone specimen cores, in most cases taken along the main loading axis of the bone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported subchondral bone plate (SBP) thinning and loss of subchondral trabecular bone (STB) in early OA [9][10][11][12] , with some suggestions that subchondral bone changes may precede changes in cartilage 13,14 . However, the hallmark features of end-stage OA comprise a thickening of the SBP 12,15,16 , together with increased bone volume fraction, increased trabecular thickness, and decreased trabecular separation in the STB [17][18][19][20] , lower bone mineralisation 21,22 and the presence of subchondral bone cysts (SBCs), and osteophytosis 23 . The aforementioned studies highlight overall trends in subchondral bone changes, but these studies have been primarily restricted to excised bone specimen cores, in most cases taken along the main loading axis of the bone.…”
mentioning
confidence: 99%
“…A limited number of studies have performed spatial analyses on bone within the human femoral head 26 . Using peripheral quantitative computed tomography (pQCT), Tamaddon, et al 22 performed a mapping of volumetric bone mineral density (vBMD) over 36 regions, relative to the region of greatest cartilage damage; reporting a decrease in vBMD immediately adjacent to overlying cartilage defects, which continued deep into the bone, but an increase in vBMD in the bone surrounding SBP. While this approach showed heterogeneous vBMD across the femoral head, nothing is known about the heterogeneity of micro-architectural parameters in the cortical and trabecular bone, considered by some the main determinants of bone quality 27 .…”
mentioning
confidence: 99%
“…Previous studies in OA hips report thicker trabeculae, higher trabecular number and increased bone volume fraction at late OA compared to early-stage OA or normal hips 13 , 20 22 . Whilst these studies have significantly enhanced understanding of bone structural changes during OA development, the reported measures are based on defined segments/biopsies extracted from the femoral head 13 , 23 25 .…”
Section: Introductionmentioning
confidence: 80%
“…In the tissue engineering field, scaffolds act as a 3D structure for supporting cell growth, providing sufficient mechanical support and provide an extracellular matrix environment for tissue regeneration [1][2][3][4][5]. To achieve success in tissue engineering, nutrient transports into the interior scaffold should be well investigated as it is one of the most significant factors in the success for a scaffold [6,7].…”
Section: Introductionmentioning
confidence: 99%